ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN ACCOUNT OFFICER PADA PERSETUJUAN PERMOHONAN PEMBIAYAAN KONSUMTIF DI PT BANK SUMUT KCP SYARIAH HM JONI - Pardede, Diah Hafni; Qarni, Waizul; Syukri, Ahmad (Jurnal Keuangan dan Perbankan Syariah, 2023)
Account Officer is a person whose job is to find eligible customers according to the criteria of bank regulations. The account officer is the spearhead of the bank in marketing its products, therefore an account officer must have adequate salesmanship to market the products offered. The purpose of this study is to analyze the factors that influence the account officer's decision on approval of consumer financing applications, as well as the factors that cause customer financing applications to be rejected at PT Bank Sumut KCP Syariah HM Joni. The method used in this research is qualitative. Methods that are not in the form of numbers obtained from recordings, observations, interviews or written materials. Data collection methods are literature study, interviews and observations and use primary and secondary data. Based on the results of the research and discussion, it can be concluded that before providing financing to customers who wish to apply for consumptive financing at Bank Sumut KCP Syariah HM Joni, the account officer must conduct an objective assessment of various aspects related to the object of financing (5C Analysis), so as to provide confidence in all parties involved.